稀土永磁传动机构的转矩计算及特性分析 - 赵韩; 陶骏; 杜世俊; 田杰; 杨文胜 (Jixie chuandong)
In this paper, based on the electromagnatic field theory, the magnetic action of the rare earth magnet gear transmission is divided into three parts, i.e. the actions between the two equivalent currents, between the equivalent current and magnetized field of the medium, between the two magnetized fields of the media. With help of the formulas of magnet field characteristics which are derived using the integral equation method, the torque formula of the magnet gear transmission is derived, and the torque features are analyzed.